(untitled) (Modern education and development, 2025)
Maintaining relatively good health for people aged 75 and over is a priority for independent and active participation in family and community life. Health promotion and disease prevention measures can prevent or delay the emergence of non-communicable and chronic diseases. In order to provide adequate care to the elderly, it is very important to train competent medical professionals and society, such as training healthcare professionals to help elderly patients, preventing and managing chronic diseases, developing sustainable long-term care strategies, and creating services and environments with favorable conditions for this patient population.